Rationale and study design of a three‐period, 58‐week trial of ferric citrate as a phosphate binder in patients with ESRD on dialysis. Issue 1 (15th June 2012) - Umanath, Kausik; Sika, Mohammed; Niecestro, Robert; Connelly, Carolyn; Schulman, Gerald; Koury, Mark J.; Lewis, Julia B.; Dwyer, Jamie P.; ,
Abstract Chronic kidney disease associated mineral and bone disorders arise as a result of aberrant bone mineral metabolism in patients with advancing levels of renal dysfunction and end‐stage renal disease. One of the cornerstones of treatment is the use of phosphate‐binding agents. We describe the rationale and study design for a clinical trial to assess the safety and efficacy of ferric citrate as a phosphate binder. This trial is a three‐period, international, multicenter, randomized, controlled clinical trial to assess the safety and efficacy of ferric citrate as a phosphate binder, consisting of a 2‐week washout period, a 52‐week safety assessment period in which subjects are randomized to ferric citrate or active control, and a 4‐week efficacy assessment period in which subjects randomized to ferric citrate in the safety assessment period are randomized to ferric citrate or placebo. Eligible subjects include end‐stage renal disease patients who have been treated with thrice‐weekly hemodialysis or peritoneal dialysis for at least 3 months in dialysis clinics in the United States and Israel. Primary outcome measure will be the effect of ferric citrate vs. placebo on the change in serum phosphorus. Safety assessments will be performed by monitoring adverse events, concomitant medication use, and sequential blood chemistries (including iron parameters, phosphorus, and calcium). This three‐period trial will assess the efficacy of ferric citrate as a phosphate binder. If proven safe and efficacious, ferric citrate will likely provide an additional phosphate binder to treat chronic kidney disease associated mineral and bone disorders.